Silver nanowire-carbon nanotube/coal-based carbon composite membrane with fascinating antimicrobial ability and antibiofouling under electrochemical assistance. (December 2020) - Xu, Yuanlu; Yuan, Yin; Fan, Xinfei; Cui, Mingrui; Xiao, Jingkun; Du, Jing; Pan, Zonglin; Feng, Guoqing; Lv, Bowen; Song, Chengwen; Wang, Tonghua
Abstract: Biofouling caused by microorganism is a serious problem that inhibits the application of membrane technology in wastewater treatment. To overcome this drawback, a novel silver nanowire-carbon nanotube/coal-based carbon (AgNW-CNT/CC) composite membrane was prepared with fascinating antimicrobial ability and electrochemically enhanced biofouling resistance. The addition of AgNWs could significantly enhance its antibacterial activity of the AgNW-CNT/CC composite membrane by releasing the silver ions or direct contact and accelerated bacterial detachment from membrane surface. The final flux of AgNW-CNT/CC composite membrane (70.5 % of its initial value) was 1.57 times higher than that for the CNT/CC membrane (45 % of its initial value) without an external voltage. Importantly, incorporating AgNWs was beneficial for electrochemical assistance, which exhibited a prominent synergistic antibiofouling performance. The flux of the cathodic AgNW-CNT/CC composite membrane was stable with acceptable flux loss (95.7 % of its initial value) under a low-voltage of 3.5 V, demonstrating the bacteria migration to the membrane surface can be inhibited by electrostatic repulsive and micro-bubbles generated via water electrolysis, thus promoting the inactivated bacteria to leave the membrane surface and avoid the formation of a biofilm, while the steady-state flux declined to 82.5 % of its initial value for electrochemically assisted CNT/CC membrane. Moreover, the regeneration of the fouled membrane can be achieved by applying an intermittent external voltage to promote the inactivated bacteria away from the membrane surface. These results suggested that the integration of electrochemistry with antimicrobial modification offers a new insight for biofouling mitigation during membrane separation.